2001
DOI: 10.1128/aem.67.1.330-338.2001
|View full text |Cite
|
Sign up to set email alerts
|

Plasmid Transfer between Bacillus thuringiensis subsp. israelensis Strains in Laboratory Culture, River Water, and Dipteran Larvae

Abstract: Plasmid transfer between strains of Bacillus thuringiensis subsp. israelensis was studied under a range of environmentally relevant laboratory conditions in vitro, in river water, and in mosquito larvae. Mobilization of pBC16 was detected in vitro at a range of temperatures, pH values, and available water conditions, and the maximum transfer ratio was 10 ؊3 transconjugant per recipient under optimal conditions. Transfer of conjugative plasmid pXO16ϻTn5401 was also detected under this range of conditions. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
49
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 28 publications
2
49
1
Order By: Relevance
“…Many cry genes are associated with transposable elements that may facilitate gene amplification, leading to the evolution of new toxins (29). In addition, most cry genes are found on plasmids, and horizontal transfer by conjugation may result in the creation of new strains with a novel complement of cry genes (166,167).…”
Section: Toxin Diversitymentioning
confidence: 99%
“…Many cry genes are associated with transposable elements that may facilitate gene amplification, leading to the evolution of new toxins (29). In addition, most cry genes are found on plasmids, and horizontal transfer by conjugation may result in the creation of new strains with a novel complement of cry genes (166,167).…”
Section: Toxin Diversitymentioning
confidence: 99%
“…However, plasmid transfer from other B. cereus group strains to B. anthracis, and vice versa, may occur under some specific conditions. It is well documented that the spores of insecticidal B. thuringiensis can germinate and then multiply in the midguts of dead target insects, and plasmid transfer at different frequencies under these conditions have been recorded previously (31,34). The large-scale application of commercial B. thuringiensis for agricultural pest control may facilitate gene exchange among B. cereus group strains in target insects and then endow the strains with insecticidal properties and wider host ranges.…”
Section: Discussionmentioning
confidence: 99%
“…Some reports have confirmed that strains of B. thuringiensis and B. cereus exhibit low degrees of clonality and that exchange of genetic material between them occurs frequently in river water (31), soil (35), food preparation environments (33), and even the guts of insects (31,37). Previous reports revealed that the toxin genes or whole toxin plasmids of B. anthracis can transfer to other Bacillus sp.…”
mentioning
confidence: 94%
“…In this context, conjugation has been extensively studied in different niches, including insect gut (20), gnotobiotic rats (28), the rhizosphere of grass plant (18), soil (24), water (21), and, most recently, dairy products (15,23). These habitats were found to variably affect the overall process of plasmid conjugation and mobilization, suggesting adaptative transfer mechanisms.…”
mentioning
confidence: 99%